Comparison of pain intensity and impacts on oral health-related quality of life between orthodontic patients treated with clear aligners and fixed appliances: a systematic review and meta-analysis - Qiuying Li; Yugui Du; Kai Yang (BMC, 2023)
Abstract Objective This study aimed to compare the pain intensity and impacts on oral health-related quality of life (OHRQoL) between orthodontic patients treated with clear aligners (CAs) and fixed appliances (FAs). Methods A systematic search was conducted up to December 2022 using PubMed, Web of Science, Cochrane Central Register of Controlled Trials, and Embase. Randomized controlled trials (RCTs) and prospective non-randomized controlled trials (non-RCTs) comparing pain intensity or OHRQoL between patients treated with CAs and FAs were included. The risk of bias (RoB) of individual studies was evaluated using the Cochrane RoB tool 2.0 and ROBINS-I tool for RCTs and non-RCTs, respectively. Further, meta-analyses were separately conducted for each included study using the total oral health impact profile (OHIP)-14 and visual analog scale (VAS) scores to evaluate OHRQoL and pain intensity, respectively. Results Overall, 12 studies (5 RCTs and 7 non-RCTs) were included in the study. Subgroup analyses conducted according to the total OHIP-14 scores revealed that patients treated with CAs had higher OHRQoL at 1 week, 1 month, and 6 months of the treatment. Meanwhile, subgroup analyses conducted according to the VAS scores revealed that pain levels were lower in the CA group only at 3 and 4 days of the treatment. Conclusions Patients treated with clear aligners had higher OHRQoL than those treated with fixed appliances during orthodontic treatment. However, OHRQoL appeared to be similar between the two groups at the end of the treatment. Moreover, patients treated with clear aligners experienced lesser pain than those treated with fixed appliances on the third and fourth day after the initial treatment. The difference in pain intensity between the two treatment modalities was not noted at other time points.